Operation Characteristics and Load Distribution of CHP Units with Extraction-Condensate and Extraction-High Back Pressure Mode - Xue LIU; Ganggang HU; Jian LI; Zhiping YANG; Ningling WANG; Zhihua GE (Zhongguo dianli)
The application of high back pressure turbine in large capacity coal-fired plants can make use of exhaust waste heat as much as possible to save fuel remarkably, which has become the first choice for heating renovation of thermal power plants if the heat load demand can be met. In this paper, the model is developed for a power plant with 2 × 330 MW high back pressure and extraction combined heat and power (CHP) units to analyze the theoretical heating capacity. Considering the supply and return water temperature of the heat supply network, peak shaving capacity and economic operation conditions are also analyzed. The steam extraction distribution and load distribution problems are studied for the operation of extraction condensate-extraction high back pressure (EC-EHBP) mode and double extraction condensate (EC-EC) mode, respectively. Principles of steam extraction distribution and electric load distribution are obtained and the back pressure operation mode is also determined under different ambient temperatures. The research results can provide theoretical guidance for the actual operation of CHP power plants.